Commercial bottom trawling as a driver of sediment dynamics and deep seascape evolution in the Anthropocene - Martín de Nascimento, Jacobo (2014)
Fishing gear and techniques have evolved through the centuries, and particularly after the Second World War, towards a mass production industry in such a scale that it has placed many commercial stocks in a delicate or depleted status. Furthermore, certain fishing methods have other undesirable side effects on ecosystems and habitats. In this work, the known impacts of bottom-dragged gear on the seafloor are reviewed. Some of the least known issues are emphasized, namely, impacts on the physical properties of deep-sea sediments, resuspension, erosion, near-bottom turbidity and seabed morphology. Due to its recurrence, mobility and wide geographical extent, bottom trawling has become an effective driver on shaping the physical basis of benthic habitats: its composition, texture and morphology at scales from micro to the entire continental margin. It is concluded that trawling is comparable in its transforming power over seascapes to the effects of agriculture or deforestation on land.